Glass Microfiber Interlayer for Polysulfide Retention in Lithium‐sulfur Cathodes - Georgina Jahan; Saeme Motevalian; Dambar Hamal; Osama Awadallah; Ana Claus; Natalia Rodrigues de Oliveira; Meer Safa; Bilal El‐Zahab (ChemElectroChem, 2024)
Abstract In this study, a glass microfibers interlayer (GMI) was used at the interface of the cathode and electrolyte in lithium‐sulfur batteries to prevent polysulfides loss from the cathode which contributes to capacity and coulombic efficiency fades during cycling. The interlayer's performance was evaluated using full‐cell studies and various visual experiments at commercially relevant sulfur areal loadings. Cells with sulfur loading of 4 mg cm−2 consistently had initial capacities exceeding 1200 mAh g−1 and reached a stable performance at around 900 mAh g−1 after 2 cycles at 2.23 mA cm−2. After 200 cycles the capacity retention remained robust at 95 %, marking an average decay rate of only 0.016 % per cycle. Cathodes with 2.8 mg cm−2 at 1.57 mA cm−2 rate and cathodes with 2 mg cm−2 at 3.3 mA cm−2 high rate exhibit improved rate capability and excellent stability over 400 cycles and 500 cycles respectively with 20 % more capacity retention than non‐GMI cells. Post‐failure analyses of the cell components revealed the GMI's role in controlling the concentration of soluble polysulfides at the anode and a suitable candidate that can be used alone or in tandem with other approaches to help overcome one of the major problems in lithium‐sulfur batteries.